Medical cost inflation and its drivers in Indonesian employer-sponsored health insurance for retiree families - Prastyo, Cahya E.; Gani, Ascobat (Narra Sains Indonesia, 2025)
Rising life expectancy and changes in disease patterns have led to an increase in retiree medical costs. Understanding these trends is essential for ensuring the financial sustainability of retiree healthcare programs. The aim of this study was to analyze medical cost inflation and its drivers in Indonesia's employer-sponsored retiree health insurance program from 2020 to 2023. A retrospective cohort study using total sampling included 29,695 retirees, analyzing medical records and insurance claims to examine demographic transition, cost analysis and relative risk of cost drivers. The study found that the retiree population is aging, characterized by longer life expectancy and a growing proportion of individuals aged above 71 years. Medical cost inflation among retirees is higher compared to the general population, driven by aging, high-cost diseases, increased healthcare utilization, and rising treatment costs. Cardiovascular diseases, diabetes, and chronic kidney disease are major drivers of high medical costs. Inpatient care is the most significant cost component, with a cost risk 14.39 times higher than clinic visits. Medicine and medical treatment are leading cost contributors in the retired population. The rising cost of retiree healthcare necessitates sustainable financing strategies. The study highlights that medical cost inflation in retirees was higher than in the general population, driven by aging, high-cost diseases, increased utilization, and rising treatment costs. Strengthening preventive care, optimizing primary care, and diversifying funding sources are recommended to ensure long-term financial stability.